Ethnomathematical Exploration in the Geulis Group Tasikmalaya West Java - Azahra, Astrid Sulistya; Munahefi, Detalia Noriza; Wijayanti, Kristina; Prabowo, Agung (Research Collaboration Community (Rescollacom), 2022)
In this study, mathematical concepts are used to explore the existence of mathematics in culture, especially in the Tasikmalaya group of geulis. By observing the current conditions, the activity of making kelom geulis is seen as a